The Mutual Influence of Religion and Science in the Human Understanding and Exploration of Outer Space - Weibel, Deana L.; Swanson, Glen E. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This collection examines the overlap between religious and scientific approaches to understanding and exploring outer space, a topic that merits continued academic study. It is the hope of the editors that these works will bring new insights and suggest new directions for investigation in this burgeoning field. Too often, religion and science are seen as diametrically opposed areas of human endeavor when, in reality, many scientists are influenced by religious ideas and many religious communities are inspired by scientific ideas. Religious activity has long been an aspect of humanity and will likely continue to accompany humans, even if or when we begin to settle outer space. We anticipate that this collection will be of use to future researchers studying the intersection of religious and scientific concepts of outer space. We would like to give our thanks to the authors whose works are included here and to note that circumstances during the very challenging year of 2020 have made it difficult for everyone who expressed interest in participating in this project. We also would like to thank our son, Luke Swanson, who was so very patient while his parents' attention was focused on "the heavens".